Hybridity in the governance and delivery of public services - Savignon, Andrea B.; Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Studies in public and non-profit governance, 2018)
This book seeks to answer the unsolved questions related to hybrid organisations, adopting a multifaceted approach focussing on different national contexts, including the UK, Italy, Australia, and Sweden, as well as global organisations. Authors consider policy sectors including humanitarian aid, local transport, healthcare, and welfare services.